Factors Affecting Dividend Policy in Manufacturing Companies on IDX in 2016-2020 (Empirical Study on Manufacturing Companies listed on the Indonesia Stock Exchange) - Ahyanna, Yolanda Onylia; Edi Surpriono (UIN Sunan Kalijaga Yogyakarta, 2023)
Research Aims: This study aims to analyze Factors Affecting Dividend Policy in Manufacturing Companies on IDX in 2016-2020(Empirical Study on Manufacturing Companies listed on the Indonesia Stock Exchange). Methodology: The dependent variable of this study is dividend policy while the independent variables are Profitability, Free Cash Flow, Firm Size, Managerial Ownership. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange in 2016-2020. The sampling technique used was purposive sampling method. Based on the selected criteria, 170 samples of manufacturing companies were obtained. This research uses multiple linear regression analysis technique. Research Findings: The results of this study indicate that: (1) Profitability has a positive and significant effect on dividend policy, (2) Cash Ratio has no effect on dividend policy, (3) Firms Size on dividend policy, (4) Managerial Ownership on dividend policy. Theoretical Contribution: This study contributes theoretically to understanding dividend policy factors in manufacturing companies on the Indonesia Stock Exchange (2016-2020), confirming dividend policy theory, considering company size, correcting cash ratio assumptions, and developing understanding of managerial ownership. Implication: implications offer practical insights for financial management, strategic decision-making, corporate governance, investor relations, and policymaking in the context of dividend policies for manufacturing companies on the Indonesia Stock Exchange.